2022
DOI: 10.3389/fped.2022.906177
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence Mapping of Schistosoma mansoni Among Pre-school Age Children in Rwanda

Abstract: Schistosoma mansoni is endemic in Rwanda, and control programs have been implemented with a special focus on school-age children (SAC), ignoring pre-school age children (pre-SAC) for which the actual prevalence of the disease is not well established. This study consisted of a cross-sectional quantitative mapping of the distribution of Schistosoma mansoni and identification of associated risk factors among pre-SAC throughout the country. The study covered all the 17 districts of Rwanda endemic for Schistosoma m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The patient originated from the highest Schistosoma endemic district of Rwanda, Nyagatare 6 and had been exposed multiple times with stagnant water by swimming according to his exposure interview. The presence of periportal fibrosis explains the chronicity of the infection while the 3-year history of abdominal complaints would likely be due to intra-abdominal Schistosoma nodules as seen by colonoscopy and abdominal CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…The patient originated from the highest Schistosoma endemic district of Rwanda, Nyagatare 6 and had been exposed multiple times with stagnant water by swimming according to his exposure interview. The presence of periportal fibrosis explains the chronicity of the infection while the 3-year history of abdominal complaints would likely be due to intra-abdominal Schistosoma nodules as seen by colonoscopy and abdominal CT scan.…”
Section: Discussionmentioning
confidence: 99%
“…Several earlier studies and predictive models focusing on the risk of schistosomiasis transmission have been based on human infections [ 26 , 27 , 41 , 45 ]. While control of schistosomiasis had previously been based on reducing morbidity among humans, understanding the distribution of snails becomes important in achieving the current disease elimination target.…”
Section: Discussionmentioning
confidence: 99%
“…Data on the infection of pre-school-aged children (PreSAC) was collected from all the 15 districts where snail sampling had been conducted. The data from a parasitological study on PreSAC [ 41 ] were used to assess and determine the link between human infection and snail distribution and infectivity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies reported a higher prevalence of S. mansoni infection in pre-SAC ranging from 11.8% to 70.5% [ 16 , 17 , 18 , 19 , 20 , 21 ], while some reported a lower rate ranging from 0.9% to 5.9% [ 15 , 22 , 23 ]. Small-scale studies reported that daily exposure to infested water bodies and high levels of cumulative water contact in habitats where snail hosts are found is linked with the risk of transmission among pre-SAC [ 8 , 24 , 25 , 26 ]. Moreover, children’s habit of swimming as well as the frequency of swimming in rivers and children’s habit of crossing rivers barefoot are associated with intestinal schistosomiasis in Ethiopia [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%